2020
DOI: 10.1074/jbc.ra120.013030
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and structural insights into how amino acids regulate pyruvate kinase muscle isoform 2

Abstract: Pyruvate kinase muscle isoform 2 (PKM2) is a key glycolytic enzyme involved in ATP generation and critical for cancer metabolism. PKM2 is expressed in many human cancers and is regulated by complex mechanisms that promote tumor growth and proliferation. Therefore, it is considered an attractive therapeutic target for modulating tumor metabolism. Various stimuli allosterically regulate PKM2 by cycling it between highly active and less active states. Several small molecules activate PKM2 by binding to its inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 50 publications
5
31
1
Order By: Relevance
“…4l ). Given that the K d of PKM2 for ADP is 200–300 µM 16 , its activity would be sensitive to this degree of ADP depletion. Indeed, we found that loss of Pkm2 (Δ Pkm2 ) in MEFs exhibit an increased shunt from glycolysis into serine synthesis relative to wild-type MEFs, and MTX treatment failed to increase serine flux in these cells despite a robust depletion of purine nucleotides Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4l ). Given that the K d of PKM2 for ADP is 200–300 µM 16 , its activity would be sensitive to this degree of ADP depletion. Indeed, we found that loss of Pkm2 (Δ Pkm2 ) in MEFs exhibit an increased shunt from glycolysis into serine synthesis relative to wild-type MEFs, and MTX treatment failed to increase serine flux in these cells despite a robust depletion of purine nucleotides Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The X-ray crystallography structure of the human pyruvate kinase M2 (PKM2) was obtained from the https://www.rcsb.org/structure6V74 [ 15 ]. Proteins were imported to a Molegro Virtual Docker [ 16 ] and prepared for docking.…”
Section: Methodsmentioning
confidence: 99%
“…Carcinogenic Ras mutations have three isotypes: HRAS, KRAS, and NRAS, which are the background of many tumorigenesis ( Kumazaki et al., 2020 ). PKM2 is highly expressed in a variety of human tumor cells, which provides favorable conditions for the survival, growth, and diffusion of tumor cells ( Nandi and Dey, 2020 ). PLK1 is overexpressed in a variety of human cancers, which can directly participate in the cell-cycle regulation of tumor cells ( Goroshchuk et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%